Earthing Method as Lifestyle Medicine to Reduce Hypertension in Pregnancy in Surakarta City, Central Java, IndonesiaEarthing Method as Lifestyle Medicine to Reduce Hypertension in Pregnancy - Estiningtyas; Anindhita Yudha Cahyaningtyas; Muhammad Akhsin Muflikhun (Journal of Health Science and Prevention, 2023)
Hypertension in pregnancy is among the three highest complications in 1 in 10 pregnant women. It is a significant cause of morbidity and mortality for mothers and babies (including seizures and low birth weight (LBW)). Earthing or grounding is a direct contact therapy between the body and the earth's surface (soil, grass, sand or stone), which allows the free transport of electrons from the earth's surface to spread to the body through the skin. The research objective was to analyze the effect of Earthing on hypertension in pregnancy. The research design was a pre-experimental with a one-group pretest and posttest, designed for one year of study. The population of pregnant women with hypertension in Surakarta City, Central Java, with the sampling technique used was purposive sampling, recruiting 20 respondents. Earthing duration 1 hour every day for 30 days. The statistical analysis results in a P-value of 0.000, t-count 25.065>t-table 2.093, for systolic blood pressure and P-value 0.000, t-count 93.05>t-table 2.093 for diastolic blood pressure. It indicates a significant difference in pregnant mothers' systolic and diastolic blood pressure before and after Earthing. It is recommended for mothers to perform Earthing or grounding as a lifestyle medicine at home by placing bare feet on the soil every day for 1 hour. It is beneficial to do Earthing/grounding throughout the pregnancy or by using Earthing device that connects the electrons in the earth to the skin.